THE EVOLUTION OF LANGUAGE AND THE DEVELOPMENT OF HUMAN THOUGHT ACCORDING TO GIAMBATTISTA VICO - Setti, Gabriel Augusto Miranda (Seven Editora, 2025)
This article aims to present the relevance and importance of the thought of the Italian philosopher, historian, and jurist Giambattista Vico. This will be achieved through the study and understanding of his analysis of the historical development of language and human thought. To this end, the article discusses a central point in his theory: the three modes of communication among peoples, based on their languages. These are: the language of the gods, the heroic language, and the language of men. The first is not necessarily a spoken language, as it is closer to original sounds and grunts. The second is an intermediate stage of development still closely tied to heroic narratives. The third, that of men, already presents characteristics that most closely resemble a properly rational and developed language. In this context, poetic wisdom, which encompasses the first two types of language mentioned above—that of the gods and the heroic language—is the first expression of understanding reality, the origin of all future languages. This reflection concludes by highlighting the importance of understanding these languages ​​as fundamental to the constitution of rational human thought itself. DOI: https://doi.org/10.56238/sevened2025.036-067